1999
DOI: 10.1038/sj.onc.1202947
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel activated form of the keratinocyte growth factor receptor by expression cloning from parathyroid adenoma tissue

Abstract: Parathyroid adenomas are benign tumors in the parathyroid glands, whose pathogenesis is largely unknown. We utilized an expression cDNA cloning strategy to identify oncogenes activated in parathyroid adenomas. An expression cDNA library was prepared directly from a clinical sample of parathyroid adenoma tissue, transfected into NIH3T3 cells, and foci of morphologically transformed cells were isolated. Following plasmid rescue, we identi®ed cDNAs for the keratinocyte growth factor receptor at a high frequency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…For expression using retrovirus, we have constructed human wild‐type FGFR2(IIIc) ( FGFR2 ( WT )) (Sakaguchi et al . 1999b), and dominant‐negative FGFR2(IIIc) ( FGFR2 ( DN )) linked to the enhanced green fluorescent protein ( EGFP ) through the IRES (internal ribosomal entry site) sequence in the pMXs‐IG vector (a gift from Dr Kitamura, University of Tokyo).…”
Section: Methodsmentioning
confidence: 99%
“…For expression using retrovirus, we have constructed human wild‐type FGFR2(IIIc) ( FGFR2 ( WT )) (Sakaguchi et al . 1999b), and dominant‐negative FGFR2(IIIc) ( FGFR2 ( DN )) linked to the enhanced green fluorescent protein ( EGFP ) through the IRES (internal ribosomal entry site) sequence in the pMXs‐IG vector (a gift from Dr Kitamura, University of Tokyo).…”
Section: Methodsmentioning
confidence: 99%
“…Two isoforms of the receptor, FGFR2b and Ksam-IIC3, which differ in the carboxy-terminal domain, have been described and have very different growth-activating properties (Ishii et al, 1995;Lorenzi et al, 1997;Sakaguchi et al, 1999). We therefore investigated the growth inhibitory properties of Ksam-IIC3, the isoform with the short carboxy-terminal domain (Figure 4a).…”
Section: The Distal Carboxy-terminal Portion Of Fgfr2b Is Involved Inmentioning
confidence: 99%
“…Two more FGFR2 isoforms make use of an alternative E18. The encoded C termini either overlap with the proximal part of the canonical FGFR2 C terminus (C2) or are different to it (C4) [16][17][18] . Thus, splicing to E18-C3 or E18-C4 generates FGFR2 isoforms that encode dysfunctional C termini resembling E18 truncation (Extended Data Fig.…”
Section: Expression Of Fgfr2 δE18 In Human Cancermentioning
confidence: 99%
“…Previous research showed in vitro transforming abilities of C-terminally truncated FGFR2 isoforms [17][18][19][25][26][27] . Our in vivo screening data and analyses of human oncogenomic datasets similarly suggested that exclusion of E18 is a critical determinant to render FGFR2 REs oncogenic.…”
Section: E18 Loss Is Key To Fgfr2 Oncogenicitymentioning
confidence: 99%
See 1 more Smart Citation